Bacterial iron acquisition by Escherichia coli is facilitated by amino acid complexation in a rapid-renewal environment - Juanita Lara-Gutiérrez; Jen Nguyen; Matthew R. McIlvin; Ichiko Sugiyama; Zachary C. Landry; Uria Alcolombri; Sammy Pontrelli; Joaquín Jiménez-Martínez; Uwe Sauer; Terence Hwa; Johannes M. Keegstra; Mak A. Saito; et al. (Proceedings of the National Academy of Sciences, 2026)
In natural environments, bacteria often encounter low concentrations of nutrient mixtures that are continuously replenished by physical processes such as fluid flow. Studying bacterial physiology under such conditions is experimentally challenging because it is difficult to maintain steady, low nutrient concentrations with rapid renewal. Most studies on nutrient limitation have used approaches such as the chemostat, which rely on long renewal times to sustain low concentrations. We developed a Millifluidic Continuous Culture Device (MCCD), inspired by microfluidics, that enables bacterial cultivation in nutrient mixtures at low micromolar concentrations with rapid renewal driven by fluid flow. Unlike microfluidic systems, the MCCD retains sufficient culture volume to support batch-scale ‘omic analyses. Using the MCCD, we cultured Escherichia coli in a mixture of amino acids and nucleobases at three concentration ranges spanning a fivefold difference in growth rates. Surprisingly, at the lowest concentration range, cells exhibited proteomic signatures of iron limitation despite equal total ferrous iron across conditions. Uptake experiments with labeled iron–histidine and iron–cysteine complexes confirmed that amino acids facilitated ferrous iron acquisition. Under continuous flow, siderophores were washed out, rendering this pathway ineffective and revealing a previously unrecognized mechanism of iron acquisition via soluble ferrous iron–amino acid complexes. These findings highlight the importance of studying bacterial physiology at low nutrient concentrations and also suggest a broader role for other organic substrates capable of complexing iron as potential iron sources in environments with rapid renewal.